Representasi Konten Kimia dalam Drama Korea “The First Responders” sebagai Media Pembelajaran - Rizky, Bintang; Milama, Burhanudin; Yanthi, Novi (Entalpi Pendidikan Kimia, 2025)
Chemistry learning media play a role in helping students understand chemistry concepts. There are many choices of learning media used in chemistry, such as films. However, films are not widely used as learning media, one of which is Korean films. This study aims to identify chemistry content that appears in drama scenes and determine the relevance of this content to chemistry material in senior high school. The analysis process refers to Charles Sanders Peirce's semiotic technique through three stages, namely sign, object, and interpretant. The validity of the findings was tested through investigator triangulation involving experts in the fields of Chemistry Education and Indonesian Language and Literature Education. The results of the inter-observer agreement coefficient calculation showed an average value of 1, which is classified as very good. Based on these findings, it can be concluded that there is a representation of chemistry concepts in the Korean drama The First Responders. The chemistry concepts represented are related to high school chemistry subject matter. This research can be used as an alternative medium in chemistry learning. Scenes in the film can be used as sparking questions, initial problems in learning activities.